1999
DOI: 10.1093/ajcn/70.3.504s
|View full text |Cite
|
Sign up to set email alerts
|

Nuts and their bioactive constituents: effects on serum lipids and other factors that affect disease risk

Abstract: Because nuts have favorable fatty acid and nutrient profiles, there is growing interest in evaluating their role in a heart-healthy diet. Nuts are low in saturated fatty acids and high in monounsaturated and polyunsaturated fatty acids. In addition, emerging evidence indicates that there are other bioactive molecules in nuts that elicit cardioprotective effects. These include plant protein, dietary fiber, micronutrients such as copper and magnesium, plant sterols, and phytochemicals. Few feeding studies have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
170
0
7

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(186 citation statements)
references
References 37 publications
7
170
0
7
Order By: Relevance
“…30,31 In addition, dietary intervention studies have failed to find a relationship between nut consumption and any increment in body weight. 32 Many reasons could explain the reported associations. Protective effect against weight gain could be attributed to the increased resting energy expenditure of this type of food item rich in protein and unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In addition, dietary intervention studies have failed to find a relationship between nut consumption and any increment in body weight. 32 Many reasons could explain the reported associations. Protective effect against weight gain could be attributed to the increased resting energy expenditure of this type of food item rich in protein and unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of inclusion of hazelnut into the human diet is partly related to the fatty acids of hazelnut oil, which is rich in MUFA (83.2%) and PUFA (9%) (Alasalvar et al, 2003c). In addition to this, as stated, there may be a number of fat-and non-fat constituents in hazelnut that may elicit additional cholesterol-lowering and cardioprotective effects (Kris-Etherton et al, 1999b). In contrast, Hyson et al (2002) observed that the effects of whole almond and almond oil on plasma lipids were not different from one another in healthy men and women.…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Smentioning
confidence: 99%
“…However, recent epidemiologic and clinical studies suggest that frequent nut consumption is associated with favorable plasma lipid profiles (Durak et al, 1999;Edwards et al, 1999;Kris-Etherton et al, 1999b;Zambó n et al, 2000;Rajaram et al, 2001;Hyson et al, 2002;Garg et al, 2003) and reduced risk of coronary heart disease (CHD), cardiovascular disease (CVD), myocardial infarction, atherosclerosis and other chronic ailments (Fraser et al, 1992;Hu and Stampfer, 1999;Sabaté et al, 2000;Albert et al, 2002;Feldman, 2002). The FDA (2003) has recently authorized a health claim about the relationship between the consumption of nuts and reduced risk of CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Many foods of plant origin (raw or processed) have been found to possess functional properties, providing not only nutrients, but also protecting the human organism against some diseases, due to the presence of various phytochemicals (e.g. antioxidants), that exert anticancer, anti-inflammatory, hypocholesterolemic and antidiabetic properties (Djousse et al 2009;Lee et al 2010;Kris-Etherton et al 1999;Tighe et al 2010).…”
Section: Introductionmentioning
confidence: 99%